Curriculum and pedagogic bases for effectively integrating practice based experiences. - Billett, Stephen (Australian Learning and Teaching Council, 2011)
This report sought to identify and appraise curriculum and pedagogic principles and practices for integrating learning experiences in practice and university settings.